2015
DOI: 10.1152/ajprenal.00516.2014
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3α regulates urine concentrating mechanism in mice

Abstract: In mammals, glycogen synthase kinase (GSK)3 comprises GSK3␣ and GSK3␤ isoforms. GSK3␤ has been shown to play a role in the ability of kidneys to concentrate urine by regulating vasopressin-mediated water permeability of collecting ducts, whereas the role of GSK3␣ has yet to be discerned. To investigate the role of GSK3␣ in urine concentration, we compared GSK3␣ knockout (GSK3␣KO) mice with wild-type (WT) littermates. Under normal conditions, GSK3␣KO mice had higher water intake and urine output. GSK3␣KO mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…In this study, we disclosed an apparent dosage-dependency of the stimulatory effect on the Li concentration and explored that the redistribution of UT-A1 already occurs at 25 m M LiCl. More recently, reports showed that the GSK3β isoform knockout mice had decreased ability to concentrate urine [11], while GSK3α knockout mice showed an increased urine output and a reduced urine osmolality under basal condition [10]. In this study, we found hypertonic stimulation could inhibit the activity of GSK3.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, we disclosed an apparent dosage-dependency of the stimulatory effect on the Li concentration and explored that the redistribution of UT-A1 already occurs at 25 m M LiCl. More recently, reports showed that the GSK3β isoform knockout mice had decreased ability to concentrate urine [11], while GSK3α knockout mice showed an increased urine output and a reduced urine osmolality under basal condition [10]. In this study, we found hypertonic stimulation could inhibit the activity of GSK3.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown that GSK3 plays an important role in diabetic nephropathy [7], polycystic kidney disease [8], and proliferative renal diseases [9]. Although it has been reported that GSK3 is involved in concentrating urine by regulating vasopressin-induced AQP2 expression and translocation to the plasma membrane [4,10,11], it is unclear whether GSK3 is also involved in hypertonicity-induced UT-A1 reorganization.…”
Section: Introductionmentioning
confidence: 99%
“…GSK3β is suggested to be important for modulating AC activity, cAMP generation, and AVP sensitivity in the CD (18). However, GSK3α knockout mice, despite having impaired AVP-induced cAMP responses in CDs, are only mildly resistant to the onset of Li-NDI (48). Similarly, in the current study, although we saw clear inhibition of GSK3 activity (as evidenced by increased phosphorylation at an inhibitory site) following Li + administration, the developed Li-NDI must be cAMP independent.…”
Section: Discussionmentioning
confidence: 99%
“…GSK3α KO mice were viable, fertile, had normal body mass [133], and no obvious skeletal defects [134], but showed increased water uptake and urine production [135], enhanced sensitivity towards insulin and glucose, reduced fat mass, and increased hepatic glycogen levels [133]. In an alternative GSK3α KO model, mice were also viable but characterized by higher body weight, heavier organs (especially brain, heart, and testis), male infertility, and slightly reduced lifespan [136].…”
Section: Gsk3 Ko Modelsmentioning
confidence: 99%